Pengaruh Ekstrak Jahe Merah (Zingiber Officinale Var. Rubrum) Dan Tempat Bertengger Dingin Terhadap Performans Ayam Broiler - Julio kristofer Sihite (CV. SINAR HOWUHOWU, 2026)
Broiler chickens are sensitive to high temperatures, which can induce heat stress and negatively impact their performance. Strategies to mitigate this risk include administering natural supplements—such as red ginger extract (*Zingiber officinale* var. *rubrum*)—and employing innovative cooling perches. This study aimed to evaluate the effects of red ginger extract supplementation and the use of cooling perches on broiler performance. The materials used included broiler chickens (198 day-old chicks), drinking water, red ginger extract, housing facilities, galvanized metal perches (for the cooling treatment), a water chiller, temperature and humidity thermometers, lighting, feed scales, and extraction equipment. A Completely Randomized Design (CRD) was employed with three treatments—P1 (no red ginger extract, no cooling perch), P2 (red ginger extract at 10 ml/L, no cooling perch), and P3 (red ginger extract at 10 ml/L plus cooling perch)—and six replicates. Observed variables included water consumption, feed intake, body weight gain, and feed conversion ratio. Data were analyzed using ANOVA; significant results were further analyzed using Duncan’s Multiple Range Test. The results indicated that the administration of red ginger extract and the use of cooling perches had no significant effect (P>0.05) on feed intake, body weight gain, or feed conversion ratio; however, they did have a significant effect (P<0.05) on water consumption. Treatment P3 (red ginger extract plus cooling perch) resulted in lower water consumption compared to P1 (no extract, no cooling perch) and P2 (red ginger extract, no cooling perch). Based on the research findings, it can be concluded that the administration of red ginger extract (*Zingiber officinale* var. *rubrum*) and the use of cool perches can enhance thermoregulatory responses and contribute to a numerically lower feed conversion ratio in broiler chickens subjected to heat stress.